Firearms : an illustrated history. - DK Publishing, Inc. (New York, New York : DK Publishing, 2014)
An historical guide to the evolution of the gun features virtual tours of the earliest muskets to modern-day military weapons and includes special sections on iconic gun-makers Colt, Smith & Wesson, Maxim, and Kalashnikov.
Includes index.
Keywords: Firearms -- History; Weapons -- History; Ammunition -- History; Firearms -- History; Weapons -- History; Ammunition -- History